Assessment of genetic diversity of rose genotypes using ISSR markers - (:unkn) unknown (My University, 2017)
0

The genus Rosa L. (Rosaceae) is an important ornamental crop with a high economic value in floriculture, cosmetics, and pharmaceutical industries. Turkey is an important country in rose cultivation with unique species and cultivars, especially for rose oil production. Breeding programs of different rose genotypes are crucial for the development of new commercial varieties. In this study, genetic relationships among the old rose cultivars locally grown in Isparta were assessed by DNA fingerprinting. Inter-simple sequence repeats markers (ISSRs) were used to investigate the genetic diversity among nineteen locally grown rose genotypes. Nineteen ISSR primers yielded a total of 413 scorable amplified fragments. Nei s genetic identity values ranged from 0.545 to 0.951. Nei s genetic distance was used to construct a dendrogram using the unweighted pair-group method with arithmetic averages (UPGMA) cluster analysis. The dendrogram grouped the nineteen rose genotypes into four distinct clusters, and the principal coordinate analysis revealed similar genetic groups. The results confirmed the usefulness of ISSR markers to assess the genetic diversity among the selected old rose genotypes for genetic conservation and plant improvement.
Keywords: Biyoloji